2014
DOI: 10.1007/s12031-014-0428-y
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA Profile in the Substantia Nigra of Parkinson’s Disease and Healthy Subjects

Abstract: The deregulation of several microRNAs (miRNAs) has been associated with neurodegenerative processes, including Parkinson's disease (PD). Our aim was to characterize the level of miRNAs in the substantia nigra (SN) of PD patients and healthy donors. This is an important issue to characterize new putative markers and therapeutic targets for PD. RNA was extracted from the SN of postmortem PD (n=8) and healthy (n=4) subjects, and the level of 733 human miRNAs was assayed with TaqMan low-density arrays (TLDAs). Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
49
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 35 publications
2
49
0
1
Order By: Relevance
“…Previous studies showed that PAK1 was regulated by several miRNAs in different cellular activities (Saydam et al, 2011;Zhao et al, 2011). promoter of survival of dopaminergic neurons, was observed downregulated in human PD brains, and miR-7 was found to regulate cell death and oxidative stress, while miR-184 and Let-7 was reported to regulate dopaminergic neuron survival and activity (Cardo et al, 2014). The Wnt signaling pathway controls the survival of neurons, involves in the development of the central nervous system, and monitors the functions of the adult nervous system .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed that PAK1 was regulated by several miRNAs in different cellular activities (Saydam et al, 2011;Zhao et al, 2011). promoter of survival of dopaminergic neurons, was observed downregulated in human PD brains, and miR-7 was found to regulate cell death and oxidative stress, while miR-184 and Let-7 was reported to regulate dopaminergic neuron survival and activity (Cardo et al, 2014). The Wnt signaling pathway controls the survival of neurons, involves in the development of the central nervous system, and monitors the functions of the adult nervous system .…”
Section: Discussionmentioning
confidence: 95%
“…More importantly the miR-200a-3p and -144-5p were showed the different expression in PD mice for the first time. Other miRNAs reported by several PD studies, such as miR-133b, -34c-5p, -205,-155, -135b, -212, -495, -193a-3p, -34b/c and -485-5p, shared the similar expression regulation with our result, but their fold-change was lower and didn't meet our inclusion criteria [59, 6163, 6870]. However, the miR-214, -124, -132, -127-5p, -146b-5p, and -16-5p reported in other PD models, were not found the different expression [26, 30, 54, 55, 57, 60].…”
Section: Discussionsupporting
confidence: 82%
“…Our data revealed that more than 644 miRNAs were detected with significant level-change in A53T mice, especially 40 miRNAs with fold-change ≥ 2. Among the 40 miRNAs, miR-542-3p, -10a-5p, -10b-3p, -141, -200b-3p, -542-3p, and -505-5p were confirmed with similar fluctuation of expression as reports [26, 30, 6668]. More importantly the miR-200a-3p and -144-5p were showed the different expression in PD mice for the first time.…”
Section: Discussionsupporting
confidence: 80%
“…The increased levels of miR‐338‐3p, miR‐30e‐3p, and miR‐30a‐3p and decreased levels of miR‐16‐2‐3p and miR‐1294 were detected (Burgos et al., 2014). In another study (Cardo et al., 2014), miR‐135b showed the most significant difference between patients and healthy donors. For the blood miRNAs in PD, Margis et al.…”
Section: Discussionmentioning
confidence: 94%
“…Although the aberrant expression of miRNAs was reported frequently in PD‐diagnosed patients (Cardo et al., 2014; Filatova et al., 2012; Hoss et al., 2016), the circulating miRNA pattern in PD has not been well defined yet. Burgos et al.…”
Section: Discussionmentioning
confidence: 99%